Upaya Mengelola Kepuasan Nasabah Melalui Dimensi Kualitas Pelayanan (Studi Kasus Pada Nasabah Bank Tabungan Negara Cabang Pekanbaru) - KHAIRANI, ZULIA (Jurnal Daya Saing, 2017)
Service quality is very important in the banking business. In addition to offering a wide range of products, improvements in terms of information technology, physical services, and non-physical services intended to improve the quality of service. To measure the level of satisfaction is necessary to know the extent to which the quality of services provided are able to create customer satisfaction. This study aims to analized how much influence the quality of service to customer satisfaction BTN Bank Branch Pekanbaru. After learning literature review, an understanding of the influence of the physical form (tangibles), reliability (reliability), assurance (assurance), responsiveness (responsiveness), and awareness (empathy) with the variables that influence can be seen as a base strategy for development customer satisfaction.The sample in this study was 100 customers of Bank BTN Pekanbaru randomized using a sampling technique accidental sampling.Statistical analysis showed that the tangibles, reliability, responsiveness, and empathy partially and simultaneously positive and significant impact on customer satisfaction Bank BTN Pekanbaru. Keywords: Customer Satisfaction, Tangible, Reliability, Responsiveness, Assurance, and Empathy